Overall Survival Benefit in Rectal Cancer After Neoadjuvant Radiotherapy and Adjuvant Chemotherapy: A Propensity-Matched Population-Based Study - Chen, Zhiju; Li, Shaowei; Wang, Yehong; Fu, Zhiming; Liu, Ning; Wang, Hao; Liu, Xin (Frontiers in Oncology, 2020)
Background: It is well known that neoadjuvant radiotherapy could reduce local recurrence followed by surgical resection. However, evidence about oncologic efficacy of radiotherapy and survival benefit of adjuvant chemotherapy after neoadjuvant radiotherapy is still lacking. Methods: This retrospective propensity score-matched cohort study identified patients with pathologically confirmed rectal cancer and receiving surgery with curative intent from the Surveillance, Epidemiology, and End Results database from 2004 through 2014. Overall survival was compared using the stratified log-rank test. Multivariate Cox regression analysis was used for identifying risk factor and developing prediction nomogram. Results: A total of 22,008 (11,004 for each group) propensity-matched patients were identified. In the context of receiving adjuvant chemotherapy after surgical resection, there was no significant difference in terms of overall survival between surgery alone group and neoadjuvant radiotherapy and surgery group, whether for stage I (log-rank test p = 0.467), stage II (log-rank test p = 0.310), or stage III (p = 0.994). In case of receiving a prior combination therapy of neoadjuvant radiotherapy and surgery, the following adjuvant chemotherapy could significantly improve overall survival for patients with stage I (log-rank test p <0.001), stage II (log-rank test p = 0.038) and stage III (log-rank test p = 0.014). Nomogram integrating clinicopathologic factors was developed to predict survival benefit associated with neoadjuvant radiotherapy. Calibration and ROC curves validated promising performance for the nomogram. Conclusion: Patients with rectal cancer underwent neoadjuvant radiotherapy yield acceptable outcomes and are more likely to benefit from adjuvant chemotherapy in terms of overall survival. These data would be evidential for advocating consistency in guideline adherence to the use of adjuvant chemotherapy after neoadjuvant radiotherapy.